Design Listenerâ€™s Needs Of â€œsenja Manjaâ€ Program From Zora Radio Using Integration Of Service Quality And Kano Model - Fathin Farcyana Safitri; Yati Rohayati; Ika Arum Puspita (eProceedings of Engineering, 2017)
Zora Radio is one of affiliation of Telkom Education Foundation known as Yayasan Pendidikan Telkom (YPT) that is a service company runs the business activities in broadcasting field. The main profit of Zora Radio comes from advertisers on the broadcast program, especially in the prime time, so Zora Radio must maximize the program in prime time to increase the number of listeners so that it will bring revenue from advertisers. Senja Manja program is included in the prime-time program, for which Zora Radio plans to develop the program according to the expectation and needs of the listener. This study aims to support the needs analysis of program listeners in Senja Manja program by Zora Radio using service quality and Kano models to improve the service quality of programs later on. This study was conducted with by identification of 23 attributes of listener needs which used to determine the needs attribute should be prioritized in the development of service program Senja Manja. Based on the results of the service quality questionnaire processing, obtained 12 needs attributes are weak attribute and 11 attribute categorized as strong attributes. Furthermore, based on the classification of Kano Model, there are 8 needs attribute that must be prioritized and 5 attribute needs that need to be improved. Recommendations are formulated based on the data processing result containing needs attributes that are prioritized and improved as true customer needs. Keywords: Zora, Need Analysis, Service Quality, Kano, Integration of Service Quality and Kano